Transplanting the European Court of Justice: The Experience of the Andean Tribunal of Justice - Osvaldo Saldías; Laurence R. Helfer; Karen J. Alter (Oñati Socio-Legal Series, 2011)
Although there is an extensive literature on domestic legal transplants, far less is known about the transplantation of supranational judicial bodies. The Andean Tribunal of Justice (ATJ) is one of eleven copies of the European Court of Justice (ECJ), and the third most active international court. This article considers the origins and evolution of the ATJ as a transplanted judicial institution. It first reviews the literatures on legal transplants, neofunctionalist theory, and the spread of European ideas and institutions, explaining how the intersection of these literatures informs the study of supranational judicial transplants. The article next explains why the Andean Pact's member states decided to add a court to their regional integration initiative, why they adapted the European Community model, and how the ECJ's existence has shaped the evolution of Andean legal doctrine and the political space within which the ATJ operates. We conclude by analyzing how the ATJ's experience informs the challenges of supranational transplants and theories of supranational legal integration more generally. DOWNLOAD THIS PAPER FROM SSRN: http://ssrn.com/abstract=1948405